Long-term Tai Chi exercise increases body stability of the elderly during stair ascent under high and low illumination*. Issue 3 (3rd July 2018) - Song, Qipeng; Wang, Shen; Wong, Del P.; Zhou, Jingyi; Sun, Wei; Zhang, Cui; Gu, Houxin; Mao, Dewei
Abstract: The effects of long-term Tai Chi exercise on body stability of the elderly during stair ascent under high and low illumination were investigated. Forty-five healthy elderly women were divided into three groups, namely, Tai Chi exercise group, brisk walking group and no-exercise control group. All the participants ascended a staircase, during which force platforms and a motion capture system collected the data. Under the high illumination, Tai Chi exercise participants exhibited higher loading rate and anteroposterior centre of pressure (COPap ) displacement as well as a lower braking impulse than no-exercise group. Under the low illumination, Tai Chi exercise participants demonstrated higher COPap and mediolateral centre of pressure (COPml ) displacements as well as lower braking and lateral impulses compared with no-exercise participants. The centre of mass (COM)ml sway in Tai Chi and no exercise participants were higher, the loading rates in Tai Chi and walking participants were higher, and the lateral impulse in no exercise participants was higher under low illumination than under high illumination. Thus, low illumination increases the risk of falling. Tai Chi participants increased their foot clearance, head inclination angle and COPap displacement under low illumination to increase their stability during stair ascent.